Views of Emotion in Adulthood: The Role of Caregiver Meta-Emotional Philosophy - Avelar, Beatriz (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
This study was intended to examine the relationship between meta-emotional philosophy in primary caregivers (PC) and meta-emotional philosophy (MEP) in an adult individual (>18 years old) who grew up in their care (participant: PA). The sample consisted of 87 college students between the ages of 18 and 45. Participants were asked to rate items from the Help vs. Hindrance View Survey based on the views of emotion they believed were held by their primary caregiver, and items from the Meta-Emotion Scale about their own perception of emotions. Our results showed that a reported hinder view of emotion in PCs was positively associated with positive meta-emotion in PAs, while negatively associated with negative meta-emotion in PAs. On the other hand, a help view of emotion in PCs was negatively correlated with positive meta-emotion in PAs. These results revealed an inverted relationship between MEP in primary caregivers and their grown-up children, which did not support findings from previous literature, or our hypotheses. Because many of the past findings are based on the effects of parental MEP in early development, additional research with an adult sample would help establish a relationship between the two variables.